Impact of Hematuria Risk-Stratification Guidelines on CT Urography Detection of Upper Urinary Tract Malignancy. - Rumball, Ian; Arenz, Andrea A.; Bennie, Barbara A.; Riherd, Jody (Applied Radiology, 2026)
Objectives and Hypothesis: CT urography (CTU) is a preferred diagnostic modality in hematuria evaluation and has the highest sensitivity and specificity for upper urinary tract malignancy, including renal cell carcinoma and upper tract urothelial carcinoma. Recent guidelines offer differing approaches to risk stratification of patients with hematuria, which may affect malignancy detection and CTU use. We hypothesize that among CTUs obtained for hematuria, there will be increased diagnostic yield for upper tract malignancy for imaging obtained in accordance with recent risk-stratification guidelines. Materials and Methods: This retrospective observational study assessed patients who underwent primary CTU for hematuria at a rural health system between January 1, 2021, and July 31, 2023. Cases were divided into microscopic and gross hematuria, and risk-stratified according to the 2020 American Urologic Association (AUA), 2023 Dutch Urological Association (DUA), and 2025 AUA guidelines. CTU, cystoscopy, and pathology reports were reviewed. Prevalence and diagnostic yield between subgroups were compared with appropriate statistical analyses. Results: Among 969 patients (mean age 65 years), CTU detected pathologically confirmed upper tract malignancy in 28 (2.9%). Diagnostic yield was not significantly higher among CTUs performed in concordance with the 2020 AUA (3.2% vs 0%; P = .4), 2023 DUA (3.4% vs 2.2%; P = .4), and 2025 AUA (3.4% vs 0%; P = .1) guidelines. Of the 274 patients for whom CTU was not recommended by the DUA guidelines, 6 had pathologically confirmed upper tract malignancy, contrasted with none for the AUA 2020 and 2025 guidelines. Conclusions: Application of risk-stratification guidelines did not significantly improve diagnostic yield of CTU detection for upper tract malignancy among patients presenting with hematuria. Despite this, risk-stratification approaches are likely warranted given poor yield in low-risk populations. Guidelines differed in the rate of recommended CTU use and the number of cases of potentially nonimaged upper tract malignancies.